URGENSI KUALITAS DAN CITRA PERGURUAN TINGGI TERHADAP KEBERLANGSUNGANNYA - Daryanto, Tri; Haryanto, Budhi (Riset Manajemen dan Akuntansi, 2020)
This study aims to examine the effects of teaching quality and college image on positive attitudes toward college and the intention to choose the college. Samples were taken as many as 200 prospective students who intend to continue study in universities, by non-random selection. The Structural Equation Model is a statistical tool selected to elaborate on the hypothesized inter-variable relationships. The test results indicate that the new model developed in this study setting is an alternative model that can be used to explain the factors forming the intention to choose a college. In this case, the intention to choose lecture proven formed by variables teaching quality, college image with mediated by attitude. Besides, the attitude has become a fully mediating variable in the relationship between teaching quality, and college image, to intention to choose a college.The results of this study are expected to explain the process of the formation of the intention to choose collage and provide insight to marketers as input in designing a development marketing strategy. This study is also expected to be developed and tested in different contexts.